(untitled) (Medical Forum Monthly, 2024)
Objectives: To study hypoglycemic properties ofpowdered plant and aqueous extract of Allium sativum (Garlic) bulbs in type-II diabetics. Study Design: Experimental human study. Place and Duration of Study: This study was conducted at the Hamdard Institute of Pharmaceutical Sciences Islamabad and Army Medical College Rawalpindi from ___. Material and Method: The study was performed on 45 humans, which were divided into 3 groups i.e. Group A, B and C. Group A comprises of 15 patients of type-II diabetes, taking no drugs for diabetes. Group B comprises of 15 patients of Type-II diabetes taking oral hypoglycemic agents with inadequate control of blood sugar levels. Group C was control group, containing 15 healthy volunteers. The study was divided into 2 phases. Initially, after baseline sampling for blood glucose and urinary glucose, all the subjects were given powdered bulbs of Allium sativum orally, at low (20 mg/kg/d), intermediate (30 mg/kg/d) and high (45 mg/kg/d) doses, for 14 days. At day 15, blood and urine sampling was done. After 1 week, all the subjects were administered aqueous extract of Allium sativumbulbs orally, at low (20 mg/kg/d), intermediate (30 mg/kg/d) and high (45 mg/kg/d) doses, for 14 days. At the end, sampling was done again. Results: Both dry powdered plant and aqueous extract of bulbs of Allium sativum (Garlic) decrease blood and urine glucose levels in type-II diabetics, especially in the groups who were taking oral hypoglycemics and had inadequate control of blood glucose previously. Conclusion: Allium sativum has significant hypoglycemic activity, particularly in high dose, and can be combined with oral hypoglycemic agents in type-II diabetics.